NITRIC OXIDE INHIBITORY ACTIVITY OF STRYCHNOS SPINOSA (LOGANIACEAE) LEAF EXTRACTS AND FRACTIONS - Isa, AI; Dzoyem, JP; Adebayo, S.A; Suleiman, M.M; eloff, JN. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The study was aimed at determining the anti-inflammatory activity of fractions and extracts obtained from Strychnosspinosa leaves on a mediator of inflammation nitric oxide (NO).Materials and Methods: Leaves were extracted with acetone and separated into fractions with different polarities by solventsolventfractionation. The Griess assay was used to determine the nitric oxide (NO) inhibitory activity. Cellular toxicity wasdetermined by "using the MTT reduction assay".Results: With the exception of the ethyl acetate fraction which had an IC50 >750 μg/mL, all extracts and fractions had significantnitric oxide-inhibitory activity. The most active being the water fraction, chloroform fraction and the dichloromethane/methanolextracts with IC50 values of 88.43 μg/mL, 96.72 μg/mL and 115.62 μg/mL, respectively. The extracts and fractions had lowcytotoxicity on macrophage U937 cell lines.Conclusion: Extracts and fractions of Strychnos spinosa leaves may be promising sources of natural anti-inflammatory agents.Findings obtained from this study showed that Strychnos spinosa leaves possess promising anti-inflammatory action and could beused in the treatment of inflammation-related conditions.